Correlation of Infraslow Oscillatory Processes in the Body as an Integral Characteristic of Human Adaptation - Doletskiy Aleksey Nikolaevich (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 11. Estestvennye Nauki, 2014)
The aim of our study was to assess synchrony infraslow rhythm (frequency of less than 1 Hz) when registering the electroencephalogram (EEG), electrocardiogram (ECG) and reoentsefalogrammy (REG) depending from the psychoemotional state. The severity of the infraslow oscillatory processes in the central nervous system, heart and circulatory system during meditation, biofeedback with heart rate control and rhythmic breathing at a given frequency was performed. The infraslow activity depending on the use of non-pharmacological methods of relaxation was evaluated. The method of determination of the dominant frequencies of the cardiovascular, neural infraslow activity (from 0.07 to 1 Hz) was used. We compared dominant frequencies of the infraslow activity in difference relaxation states. The specific frequencies in different types of relaxation in the cardiovascular and neural systems were found. The severity of the infraslow activity correlates with the functional state of the nervous and cardiovascular systems. We found the syncronization frequency of 0.2 Hz, which is different from the frequency of cardiorespiratory synchronization of 0.1 Hz, commonly found in literature.